2002
DOI: 10.4321/s0212-71992002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Paraplejia por hipopotasemia secundaria a diarrea aguda

Abstract: RESUMENLa hipopotasemia puede dar una clínica variada pero es frecuente que curse de forma asintomática o con síntomas inespecíficos si es de escasa cantidad. En nuestro medio las causas de la hipopotasemia son variadas pero una de las etiologías más frecuentes en paises en vías de desarrollo son los cuadros diarreicos. Presentamos un cuadro de hipopotasemia severa debida a diarrea que se manifestó con intensa clínica neurológica pero que mejoró espectacularmente con tratamiento habitual.PALABRAS CLAVE: Hipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Muscle paralysis can occur with severe potassium shortage 16 . In a case series, Ortuno et al observed hypokalemic caused paralysis due to acute diarrhea 17 . Our findings also show that when diarrhea is present, hypokalemia is more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle paralysis can occur with severe potassium shortage 16 . In a case series, Ortuno et al observed hypokalemic caused paralysis due to acute diarrhea 17 . Our findings also show that when diarrhea is present, hypokalemia is more pronounced.…”
Section: Discussionmentioning
confidence: 99%